A Phase Ib Study of the Simmitecan Single Agent and in Combination With 5-Fluorouracil/Leucovorin or Thalidomide in Patients With Advanced Solid Tumor - Zhang, Qi; Deng, Ting; Yang, Fen; Guo, Weijian; Liu, Dan; Yuan, Jiajia; Qi, Changsong; Cao, Yanshuo; Yu, Qiuqiong; Cai, Huiming; Peng, Zhi; Wang, Xicheng; et al. (Frontiers in Pharmacology, 2022)
Background: Simmitecan is a potent inhibitor of topoisomerase I with anti-tumor activity. This phase Ib trial was conducted to investigate the safety and anti-tumor effect of simmitecan alone or in combination with other drugs. Methods: Eligible patients with advanced solid tumor had no further standard treatment options. Patients were allocated to receive: simmitecan alone, simmitecan in combination with 5-fluorouracil (5-FU)/leucovorin (LV), or simmitecan in combination with thalidomide, 14 days a cycle, until disease progression (PD) or unacceptable toxicity occurred. Results: A total of 41 patients were enrolled, with a median age of 55 (range 29-69) years. Among them, 13 patients received simmitecan monotherapy, 10 received simmitecan + 5-FU/LV and 18 received simmitecan + thalidomide. No dose limiting toxicity occurred. Overall, the most common grade 3/4 adverse event (AE) was neutropenia (46.2%, 70.0% and 88.9% respectively in simmitecan, simmitecan + 5-FU/LV and simmitecan + thalidomide cohorts), and treatment-related severe AEs included anemia and febrile neutropenia (7.7% each in simmitecan cohort), diarrhea (10% in simmitecan +5-FU/LV cohort), febrile neutropenia (5.6% in simmitecan + thalidomide cohort). The majority of patients (24/41, 58.3%) had progressed on prior irinotecan, nevertheless, partial response was achieved in one colorectal cancer patients treated with simmitecan + thalidomide. Disease control rates of simmitecan, simmitecan + 5-FU/LV and simmitecan + thalidomide cohorts were 46.2%, 80.0% and 61.1% respectively. Conclusions: This study demonstrated a manageable safety profile of simmitecan as a single agent or as part of a combination therapy; There have not been any safety concerns with simmitecan in combination when compared to simmitecan alone. Simmitecan + 5-FU/LV regimen seemed to have a better efficacy. Nonetheless, the efficacy of this regimen needs to be further explored in the subsequent study.